2022
DOI: 10.1177/0271678x221133972
|View full text |Cite
|
Sign up to set email alerts
|

The many layers of BOLD. The effect of hypercapnic and hyperoxic stimuli on macro- and micro-vascular compartments quantified by CVR, M, and CBV across cortical depth

Abstract: Ultra-high field functional magnetic resonance imaging (fMRI) offers the spatial resolution to measure neuronal activity at the scale of cortical layers. However, cortical depth dependent vascularization differences, such as a higher prevalence of macro-vascular compartments near the pial surface, have a confounding effect on depth-resolved blood-oxygen-level dependent (BOLD) fMRI signals. In the current study, we use hypercapnic and hyperoxic breathing conditions to quantify the influence of all venous vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…On the other hand, superficial layers (pial surface) exhibit significant differences in the topology of the large vessels, leading to a less uniform fingerprint BOLD signal change in these layers. However, these simulation results support the necessity of addressing the bias of large vessels toward the pial surface in laminar fMRI data, for example, through filtering and/or normalization techniques 51,56 .…”
Section: The Laminar Bold Fmri Signal Is Dependent On Pulse Sequence ...mentioning
confidence: 66%
“…On the other hand, superficial layers (pial surface) exhibit significant differences in the topology of the large vessels, leading to a less uniform fingerprint BOLD signal change in these layers. However, these simulation results support the necessity of addressing the bias of large vessels toward the pial surface in laminar fMRI data, for example, through filtering and/or normalization techniques 51,56 .…”
Section: The Laminar Bold Fmri Signal Is Dependent On Pulse Sequence ...mentioning
confidence: 66%
“…4). Since GRASE acquisition was utilized to generate T2-weighted BOLD contrast, we observed a plateau from middle to superficial layers with relatively lower amplitudes (∼5.5%) compared to EPI BOLD signals (∼14%) (Guidi et al, 2016; Schellekens et al, 2023). To the best of our knowledge, no study has reported detailed laminar profiles of β at 7T, while β is usually assumed to be 1 for UHF studies when the venous signal becomes negligible in extravascular BOLD signals (Griffeth & Buxton, 2011; Kida et al, 2000; Krieger et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…This layer-specific vascular response may reflect the complex architecture of cortical vasculature probed by VASO and ASL. CBV changes reflect hypercapnia-induced vasodilation in both macro- and micro-vasculature, where CBV sampled from macro-vasculature (arterioles) are hypothesized to increase from deep to superficial layer but not for the micro-vasculature compartment (capillaries) (Schellekens et al, 2023). ASL signal primarily originates from capillary vessels, and peak of CBF increase in the deep layer is consistent with the higher microvascular density in middle to deep cortical layers (Shao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…During functional experiments, neurovascular coupling induces a CBV increase primarily in large veins and small arteries, which are much more capable at dilation than microvessels. 16 Consequently, our hyperoxia experiment might underestimate macrovascular contamination - and over-estimate the microvascular specificity - compared to an other-wise equivalent functional experiment.…”
Section: Methodsmentioning
confidence: 92%